Evaluasi Kualitas Pembelajaran Online Menggunakan Media Microsoft Teams Selama Pandemik COVID-19: SMA Negeri 17 Makassar - Rizal Bakri; Niken Probondani Astuti; Nabila Putri Fiamanila (Celebes Computer Science Journal, 2021)
This study aims to measure student satisfaction with online learning services provided by teachers using Microsoft Teams during the Covid-19 pandemic. The research method used in this research is the Customer Satisfaction Index (SCI) method with attribute measurement of satisfaction using the Servqual method which consists of five dimensions of education services. Furthermore, to see the priority scale on these attributes, the Importance Performance Analysis (IPA) method is used. The results showed that SCI values ​​for the five service dimensions, namely Reliability, Responsiveness, Assurance, Empathy, and Learning Quality obtained the criteria of Very Satisfied. While the priority analysis produces attribute mapping that can be used by teachers to improve the learning process.